The Role of Work Motivation in Moderating the Influence of Competence, Workload, and Organizational Support on the Performance of Intelligence Employees at the Lima Puluh Kota Police Station - Putra, Deby Kurnia; Sari, Delfia Tanjung (Management Institute Faculty of Economics Universitas Andalas, 2025)
This study examines the role of work motivation as a moderator of the effects of competence, workload, and organizational support on the performance of Intelligence and Security personnel (Intelkam) at the Lima Puluh Kota Police Resort. Employing a quantitative explanatory survey design, the study surveyed the entire Intelkam personnel population using Likert-scale questionnaires. Data were analyzed through Partial Least Squares Structural Equation Modeling with SmartPLS. Findings indicate that competence, workload, organizational support, and work motivation did not have statistically significant effects on personnel performance in the tested model. Moreover, work motivation did not significantly moderate the relationships between competence, workload, or organizational support and performance. These results suggest that other factors—such as leadership, organizational culture, facilities, and field task dynamics—may better explain performance variation in the Intelkam context. Recommendations include adding additional predictors and employing qualitative methods to better understand operational dynamics; practical implications urge institutional review of training programs, workload management, and enhancement of tangible organizational support to improve performance.